“I worry about Mum dying” Children and their parents’ cancer diagnosis - Alexander, Elise Soyeon (Curtin University, 2022)
This thesis explored how children are affected by their parents’ cancer diagnosis. Combining symbolic interactionism and ecological systems theory revealed children were invisible to health professionals and parents were overwhelmed, rendering children undetected and their needs not supported. Children were worried and distressed due to their inability to comprehend their parents’ diagnosis, needing someone to talk to, and being disconnected from supports. These findings informed the development of the Alexander's Children’s Cancer Communication (ACCC) model.